Internet-based cognitive-behavioral therapy (CBT) for depressive symptomatology in individuals with type 1 diabetes (WEB_TDDI1 study): a randomized controlled trial protocol - Carreira-Soler, Mónica; Ruiz de Adana Navas, María Soledad; Pinzon-Martín, José Luis; Anarte-Ortiz, María Teresa (Public Library of Science, 2022)
Background Professionals need adequate tools to help patients with diabetes and depression. Although web programs integrating cognitive-behavioral therapy with diabetes education have shown good results, no similar approach has been performed as yet in Spain. The objective is to develop an Internet-based program for the treatment of mild-moderate depressive symptomatology in individuals with type 1 diabetes (WEB_TDDI1 study) based on Cognitive-behavioral therapy (CBT) and assess its results. Methods A 2-arm randomized controlled trial will be conducted. Adults with type 1 diabetes and mild-moderate depressive symptoms will be screened to participate in the study and randomly assigned to either the treatment group (TG) that will use a Web-based application for a specific 9-week intervention in depression and type 1 diabetes or the control group (CG) that will be on the waiting list during that time. Results Data on the primary variable (depressive symptoms) and secondary variables (treatment-related distress, anxiety, fear of hypoglycemia, quality of life, treatment adherence, coping strategies and glycemic control) will be collected from the TG at the beginning/baseline, at the end of treatment and at 3, 6 and 12 months after treatment. The CG will be assessed at the beginning and at the end of the TG intervention. On completion of the program by the TG, the treatment will then be carried out in the CG. Conclusions The new web application developed is expected to be effective for the treatment of mild-moderate depressive symptoms in adults with type 1 diabetes, reducing depressive symptoms and improving the rest of the analyzed variables.
Keywords: Diabéticos - Aspectos psicológicos; Depresión mental; Type 1 diabetes; Internet-based CBT; Depressive symptomatology